234k views
1 vote
Pls answer... It is in the image.

Pls answer... It is in the image.-example-1
User Zhun Chen
by
6.3k points

1 Answer

2 votes

Explanation:

2,


(a.y^(3) +3y^(2) -3 ) = (ay^(2) +(4a+3)y +4(4a+3))(y-4) +64a+45

so A = 64a +45

(
2y^(3) -5y+a =(2y^(2) +8y +27)(y-4) +108 +a

so B = 108 +a

2A-B=0--> 2(64a+45)-108-a=0--> a =18/127

3,

(3x+2y)^3 = 27x^3 +54x^2.y + 36x.y^2 +8y^3 = 27x^3 +8y^3 +2 +18xy(3x +2y) = 20^3

so P = 27x^3 +8y^3 = 20^3 - 18.xy(3x+2y)= 7440

User RedAllocator
by
5.4k points